Trends in HPV-positive cervical cancer prevalence: a retrospective study from 2013 to 2020 - Xiaohui Yang; Shiyuan Qi; Liyan Dai; Qingjian Ye; Xiaomao Li (Virology Journal)
Abstract Background Cervical cancer ranks as the fourth most common cancer among women globally, mainly linked to persistent high-risk HPV infection. In China, significant challenges persist, notably the low rates of HPV vaccination and a substantial case burden. This study retrospectively examined HPV-related cervical cancer data from a tertiary hospital spanning the years 2013 to 2020, to evaluate annual and age-specific incidence trends and offer insights for prevention and treatment strategies. Methods The retrospective analysis encompassed patients who utilized the gynecological outpatient and inpatient services at the Third Affiliated Hospital of Sun Yat-sen University from 2013 to 2020. HPV genotyping, covering 21 subtypes, was conducted using hybrid capture–based assays. The assessment of cervical biopsy disease etiology was performed by a senior pathologist. Results During the study period, a total of 9,194 cases of HPV-positive individuals were identified, among which 479 cases (5.21%) were diagnosed with cervical cancer. From 2013 to 2020, there was a statistically significant decline in the overall incidence of HPV-positive cervical cancer (Z=-4.061, P < 0.001), as well as in the incidence of squamous cell carcinoma (Z=-4.595, P < 0.001). However, the incidence of adenocarcinoma did not exhibit a significant change (Z = 0.118, P = 0.906). Regarding age distribution, a significant decrease in cervical cancer incidence was observed in patients aged 36 to 64 years (Z=-2.658, P = 0.008). In contrast, the incidence remained relatively stable in patients aged 65 years and older (Z = 0.071, P = 0.943). The incidence of squamous cell carcinoma increased with age, peaking at 27.06% in individuals over 65 years. Conclusion The decline in HPV-positive cervical cancer cases highlights the success of China’s screening and post-2016 vaccination efforts. However, rising HPV infections in younger women and ongoing cancer risks in older groups emphasized the need to broaden adolescent vaccinations, sexual health education, and lifelong screening.